Bacterial Migration Cell - Spector, Mario (2015)
Infected prostheses are usually removed from patients when this infection is difficult or impossible to treat. In this context, an unprecedented physical phenomenon, “bacterial cell migration”, by which bacteria from an infected plate is migrated to a clean one has been observed and studied at the UTN FRP Materials Laboratory. This transference is obtained when two facing plates with definite chemical and metallurgic properties, one colonized with a microorganism and the other sterile, are faced to each other in an electrically conductive liquid. For the purposes of the present study, two different cultures have been used: yeast and Staphylococcus aureus, which is one of the bacterium that causes most hospital infections. It is expected that with the implementation of this method, infected prostheses in patients can be completely cleaned in the near future.